Pengaruh Kemudahan Bertransaksi, Kepercayaan Konsumen, Dan Persepsi Resiko Terhadap Keputusan Pembelian Konsumen Pada E-Commerce Saat Pandemi Covid-19: Studi Kasus Pada Tokopedia - Sahdi, Muhammad Ferdian Armala; Mulyana, Mumuh; Tobing, Maju Lumban (Jurnal Informatika Kesatuan, 2021)
The purposes of this study are: 1) To explain and analyze the ease of transactions which have a significant effect on purchasing decisions of E-Commerce consumers during the Covid-19 pandemic, 2) To explain and analyze consumer trust which has a significant effect on purchasing decisions of E-Commerce consumers during a pandemic. Covid-19, 3) To explain and analyze risk perceptions that have a significant effect on E-Commerce consumer purchasing decisions during the Covid-19 pandemic, 4) To explain and analyze the ease of transactions, consumer confidence, and risk perceptions together have a significant effect on decisions E-Commerce consumer purchases during the Covid-19 pandemic. This study uses independent variables (ease of transactions, consumer confidence, and risk perception) and the dependent variable (purchase decisions). The data analysis technique used in this research is a quantitative approach. The object of this research is 100 respondents who have made a purchase transaction at E-Commerce Tokopedia during the covid-19 pandemic (starting from March 2020). To analyze and process the data, this study uses SPSS version 26. The results of hypothesis testing: 1) Ease of Transactions has no significant effect on Purchase Decisions (Y), 2) Consumer Trust (X2) has a significant effect on Purchase Decisions (Y), 3) Risk Perception (X3) has a significant effect on Purchase Decision (Y), 4) Ease of Transaction (X1), Consumer Trust (X2), and Risk Perception (X3) together have a significant effect on Purchase Decision (Y) (by looking at F-count result is greater than F-table). Keywords : Ease of Transactions, Consumer Trusts, Risk Perceptions, Purchase Decisions.